Waste Reduction Strategy in Upstream Through Community Participation and Modernisation of Waste Bank in Depok City, West Java Province, Indonesia - Imam Budi Hartono; Chotib; Sidik Mulyono; Desy Widya Astuti (GoAcademica Research & Publishing, 2022)
Depok city with more than 2 million people is an example of a city in a developing country facing complex urban problems. Solid waste handling is one of the critical issues in the city. More than 1,500 tons of waste are generated every day, and currently, the leading landfill site receives approximately 70% of the waste in the city. The purpose of this paper is to present a comprehensive waste management strategy for waste reduction in Depok City through community participation and modernisation of the local waste bank. The study combined qualitative data collection; interviews and direct observation in the two (2) waste bank, quantitative survey (Multinomial Logistic Regression method) with 319 waste bank managers, and 423 respondents from 11 sub-districts in Depok City. Infrastructures and socialisation are the two (2) variables that affect significantly towards modernisation of the waste bank. Meanwhile, in the context of community participation, only 36% of the respondents process their own household waste. Studies on the waste management subject are extensive, but this paper only discusses two (2) elements; community participation and modernisation of the waste bank. Extending more relevant elements of waste management will have contributed to the sustainability of the environment. This research complements references from previous studies that discuss sustainable waste management. It is hoped that the sustainable waste management strategy in Depok City can be an excellent example for other cities in other developing countries.